Determination of chlorantraniliprole and penoxsulam residues in rice by QuEChERS-UPLC-MS/MS - HUANG Zijie; HUANG Pengmian; LUO Kuanneng; XIANG Zhongping; ZHANG Honggang (Shipin yu jixie, 2024)
Objective: To establish a new QuEChERS-ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for the detection of chlorantraniliprole and penoxsulam residues in rice. Methods: After the sample was extracted with 0.2% formic acid-acetonitrile, purified with N-propylethylenediamine (PSA) and graphitized carbon black (GCB) packing, 0.2% formic acid water and acetonitrile were used as mobile phases for gradient elution, and then subjected to C18 chromatography. UPLC-MS/MS was used to column separation and determination. Results: The limits of quantification (LOQ) of chlorantraniliprole and penoxsulam were both 0.004 mg/kg, and the method detection limits (LOD) were both 0.001 mg/kg. Chlorantraniliprole and penoxsulam had a good linear relationship in the range of 0.002~0.5 mg/L, and their coefficient was greater than 0.993. At the addition levels of 0.05, 0.1, and 0.5 mg/kg, the average recovery rates of chlorantraniliprole and penoxsulam were 86% to 110% with the relative standard deviations (RSD) of 1.5% to 6.1%. Conclusion: This method is efficient and simple, has good stability and high sensitivity, and is suitable for the detection of chlorantraniliprole and penoxsulam in rice.